Daniel-François-Esprit Auber Les Diamants de la coronne (I diamanti della corona/The Crown Diamonds) Opéra-Comique en trois actes Paroles de Eugène-Augustin Scribe et Jules-Henri Vernoy de Saint-Georges In Italian and English translation. - Letellier, Robert Ignatius (Cambridge Scholars Publishing, 2014)
Daniel-François-Esprit Auber (1782-1871) was long considered one of the most typically French, as well as one of the most successful, opera composers of the nineteenth century. Although musically gifted, he initially chose commerce as a career, but soon realized that his future lay in music. He studied under Cherubini, and it was not long before his opéra-comique La Bergère Châteleine (1820), written at the age of 38, established him as an operatic composer. Perhaps the greatest turning point ...